Embedded Security in Cars Securing Current and Future Automotive IT Applications - Lemke, Kerstin; Paar, Christof; Wolf, Marko (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Most innovations in the car industry are based on software and electronics, and IT will soon constitute the major production cost factor. It seems almost certain that embedded IT security will be crucial for the next generation of applications. Yet whereas software safety has become a relatively well-established field, the protection of automotive IT systems against manipulation or intrusion has only recently started to emerge. Lemke, Paar, and Wolf collect in this volume a state-of-the-art overview on all aspects relevant for IT security in automotive applications. After an introductory chapter written by the editors themselves, the contributions from experienced experts of different disciplines are structured into three parts. "Security in the Automotive Domain" describes applications for which IT security is crucial, like immobilizers, tachographs, and software updates. "Embedded Security Technologies" details security technologies relevant for automotive applications, e.g., symmetric and asymmetric cryptography, and wireless security. "Business Aspects of IT Systems in Cars" shows the need for embedded security in novel applications like location-based navigation systems and personalization. The first book in this area of fast-growing economic and scientific importance, it is indispensable for both researchers in software or embedded security and professionals in the automotive industry.